2021
DOI: 10.1002/slct.202004528
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Benzene Derivatives as Guest Molecules on Semiconductor Properties of MOF‐199

Abstract: A metal organic framework, MOF‐199, has been synthesized under solvothermal conditions. Powder X‐ray diffraction (PXRD) pattern, Fourier‐transform infrared spectra (FT‐IR) and scanning electron microscopic images (SEM) confirmed the formation of the expected MOF‐199 structure. The semiconductor properties of MOF‐199 were then fine‐tuned by introducing three benzene derivatives as guest molecules (aniline, m‐aminobenzoic acid and p‐benzoquinone). Modified MOF‐199 samples were characterized using PXRD and FT‐IR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In the field of modern electronics, FT-IR spectroscopy is used primarily for the qualitative assessment of the composition of semiconductor materials [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Semiconductorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of modern electronics, FT-IR spectroscopy is used primarily for the qualitative assessment of the composition of semiconductor materials [ 96 , 97 , 98 , 99 , 100 , 101 , 102 ].…”
Section: Semiconductorsmentioning
confidence: 99%
“…Research on the doping of semiconductors with organic compounds should be considered interesting. Studies in this field for aniline, m -aminobenzoic acid and p -benzoquinone are summarised in the article [ 98 ]. The degree of doping of metallic spatial lattices was assessed using FT-IR.…”
Section: Semiconductorsmentioning
confidence: 99%
“…Le Ouay et al [61] prepared MIL-101(Cr)⊃ PEDOT with different polymer contents by introducing uniformly dispersed EDOT monomers in MIL-101(Cr) by evaporating the solvent, followed by oxidative polymerization in the pores by iodine vapor to obtain PEDOT. It was found that PEDOT belongs to a P-type semiconductor and can be used for NO 2 detection [264][265][266][267][268]. PEDOT mainly functions as an active and conductive material here.…”
Section: Application Of Composites Obtained By Doping Polymers In Mof For Gas Sensing and Gas Adsorptionmentioning
confidence: 99%
“…Moreover, the inherent coordination between metals or metal clusters and organic linkers in MOFs provides great flexibility in modulating their semiconductor properties to enhance the sensitivity of light collection and light response. 15 In particular, titanium in MIL-125-NH 2 can be reversibly switched between the two oxidation states (Ti 4+ and Ti 3+ ), providing the opportunity to employ MIL-125-NH 2 oxidase mimicking materials for developing colorimetric sensors. On the other hand, Pd nanocrystals show excellent oxidase and peroxidase-like catalyze activities.…”
Section: Introductionmentioning
confidence: 99%